Age stratification in collective readings of Present Day English every-DPs - Schlotterbeck, Fabian; Berezovskaya, Polina (Proceedings of the Amsterdam Colloquium, 2024)
We present an experimental study on English determiner phrases (DPs) containing every in combination with collective sentence predicates. The experiment is based on the hypothesis that every-DPs are undergoing semantic change towards a referential plural interpretation. The results support this hypothesis. In particular, change in progress is visible from variable acceptability depending on the type of predicate, and an age gradation effect. In addition, the results indicate that there is an unexpected asymmetry between collective interpretations with every-DPs in subject vs. object position.